Young females with hallux valgus show lower foot joint movement stability compared to controls: An investigation of coordination patterns and variability. (April 2022) - Kawakami, Wataru; Iwamoto, Yoshitaka; Takeuchi, Yasutaka; Takeuchi, Ryosuke; Sekiya, Junpei; Ishii, Yosuke; Takahashi, Makoto
Abstract: Background: A kinematic coupling relationship exists between foot joints during gait. In individuals with hallux valgus, forefoot or hallux kinematics may be affected by adjacent or nonadjacent joint motion. Thus, this study aimed to investigate the foot joint coordination pattern and variability during gait in young females with hallux valgus. Methods: Twenty-five young females with hallux valgus and 25 healthy young females without hallux valgus were enrolled. Reflective markers were attached according to a multisegment foot model. Kinematic data were obtained using a three-dimensional motion analysis system. Joint angles between distal and proximal segments were calculated using analysis software. Foot joint coordination pattern and variability were assessed using a vector-coding technique. Findings: Individuals with hallux valgus had a larger rearfoot relative to shank eversion and forefoot relative to midfoot dorsiflexion during terminal stance and pre-swing compared with those without hallux valgus. There were no significant differences in coordination patterns, but the consistency of coordination between the rearfoot relative to shank motion in the frontal plane and forefoot relative to midfoot motion in the sagittal plane during terminal stance was greater in the hallux valgus group than in the control group. Interpretation: The soft tissue composing the first ray might suffer from more severe stress due to the large motion that occurred with low variability in individuals with hallux valgus. This finding may suggest that the altered kinematics and coordination variability in foot joints are related to hallux valgus biomechanical etiology. Highlights: We investigated foot joint coordination in young females with hallux valgus. Coordination pattern and variability were assessed using vector-coding technique. Young females with hallux valgus exhibit altered joint coordination variability. Altered coordination variability may be related with progression of deformity.